Global Dynamics of Bird Migration: Trends, Mechanisms and Conservation Challenges - Golder, Papiya; Sadhu, Maitrayae (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Global bird migration is a complex phenomenon influenced by a multitude of factors, including climate change, habitat loss, and human activities. This paper explores the trends in migratory patterns observed over recent decades, highlighting shifts in timing, routes, and species distributions Bird migrations are behavioural occurrences, exemplifying intricate spatiotemporal tactics to optimise living expenses while enhancing fitness. Birds express a range of migratory patterns, from highly predictable obligate migration, to less predictable nomadic and fugitive migrations. Despite significant advancements in bird migration studies, still certain essential gaps remain. Due to technological advancement, bird migration studies have uncovered significant insights into the behavioural, cognitive, physiological, and evolutionary underpinnings. The seasonal variability of bird populations presents an intriguing phenomenon for avid observers to discern their origins, migratory routes, and return patterns. Among the remarkable migrations executed by several species of fish, animals, and insects, birds exemplify the highest degree of mobility among all living forms on Earth. This paper gives reasons for all Bird migration strategies with a view toward the preservation of Bird ecosystems and assurance of Environmental sustainability.